Opening and Manipulating the Gap in Graphene - Pooja Rani; Kavita (Research Highlights in Science and Technology Vol. 1, 2023)
Graphene- the charismatic material of 20th century has drawn a great amount of attention from researchers across different fields. Its two-dimensional structure and unusual electronic band structure, high carrier mobility, high electrical and thermal conductivity make it a perfect material for many applications in electronics, optoelectronics and sensors. But the absence of the energy gap prevents application of graphene in its pristine form in switching devices. A number of techniques have been developed for opening and manipulating band gap at the so-called Dirac point in graphene. This review summarizes the developments in different methods to introduce a band gap in graphene in detail.